2012
DOI: 10.1016/j.visres.2012.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative response and cortical activity during sustained attention

Abstract: Greater accommodative lag and vergence deficits have been linked to attentional deficits similar to those observed in Attention Deficit Hyperactivity Disorder (ADHD). The purpose of the present study was to assess the effect of accommodative-vergence stress on a measure of sustained attention (Conners CPT) used in the diagnosis of ADHD. Twenty-seven normal non-ADHD adults completed the Conners CPT twice: wearing -2.00 D lenses and normally (without the -2.00 D lenses) in a counterbalanced order with at least 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…Many of the children with CI report attention problems [ 36 , 41 ] and recent studies demonstrate a relationship between CI and ADHD [ 19 ]. Our study supports the finding of binocular vision as an important factor in attention [ 42 ], and the idea of deficient binocular vision in ADHD children [ 19 ]. However, CI occurs at close distances whereas in our study the used target distances fall well outside the range of distances of CI for children.…”
Section: Discussionsupporting
confidence: 91%
“…Many of the children with CI report attention problems [ 36 , 41 ] and recent studies demonstrate a relationship between CI and ADHD [ 19 ]. Our study supports the finding of binocular vision as an important factor in attention [ 42 ], and the idea of deficient binocular vision in ADHD children [ 19 ]. However, CI occurs at close distances whereas in our study the used target distances fall well outside the range of distances of CI for children.…”
Section: Discussionsupporting
confidence: 91%
“…8 In patients with ADHD, binocular vision changes and oculomotor deficits such as convergence insufficiency 9,10 , accommodative dysfunction 11 , reduced stereoacuity 12 , and ametropia 13 have been reported. Regarding underlying mechanisms, Poltavski et al 14 suggested a bidirectional relationship between attention and accommodation. However, the association between ADHD and oculomotor control changes such as accommodative dysfunction and convergence insufficiency is not clearly known yet.…”
Section: Introductionmentioning
confidence: 99%
“…In order to control for any residual refractive error, the lag of accommodation was corrected by subtracting the baseline static refractive value using the equation of Poltavski et al (2012). 58 The mean residual spherical equivalent refractive error was + 0.21 AE 0.25 D (range -0.32 to + 0.57 D). The variability of accommodation and pupil diameter were obtained by calculating the standard deviation of the dynamic accommodation and pupil recordings during a 60-s period.…”
Section: Assessment Of Accommodative Response and Pupillary Dynamicsmentioning
confidence: 91%